La política fiscal en economías exportadoras de materias primas: Evidencia para Argentina - Luis N. Lanteri (Atlantic Review of Economics, 2016)
– This paper analyzes the impact of external price shocks on fiscal policy in Argentina during the last two decades. The paper evaluates, through VAR models with long-term restrictions, the effects of the terms of trade, and the output gap, in revenues, expenditures and the primary fiscal deficit, for the period 1993-2015. The estimation results show that the fiscal policy would have been pro cyclical, since the expenditures and the primary fiscal deficit of the national government increased during periods of boom in commodity prices. The terms of trade and inflation rates would be more important, than shocks in the output gap, to explain the volatility of fiscal ratios, in the long run.
Keywords: C32; E62; Q33; 330; Argentina; terms of trade; fiscal policy; SVAR models